Treatment of acute complicated pancreatic pseudocysts - I. A. Kryvoruchko; N. M. Goncharova; V. F. Gontar (Kazimierz Wielki University, 2017)
The results of surgery in 70 patients with acute complicated pancreatic pseudocysts in age from 21 to 79 years were analyzed. For patients using an individualized medical - diagnostic campaign, which primarily was aimed at the elimination of complications following treatment with most of the pseudocyst in the long-term. In most cases, using percutaneous drainage for the purpose of the stabilization patient's general well-being, the possibility of the influence on the development the sepsis and severe organ dysfunction. If found impossible using this minimally invasive methods, and only when it is impossible to use them, or the development of complications after surgery, or results are unsatisfactory, performed "open" surgery. Mortality in complicated acute pseudocysts was 3.4 %.